Carbon nanotubes and silver nanoparticles modification of PVDF membranes for improved seawater desalination in direct contact membrane distillation - Mpala, Tshepiso J.; Richards, Heidi; Etale, Anita; Mahlangu, Oranso T.; Nthunya, Lebea N. (Frontiers in Membrane Science and Technology, 2023)
Membrane distillation (MD) has emerged as a novel technology capable of recovering fresh water from brackish, saline, and wastewater. However, its industrial application is limited to various challenges including membrane properties. In this work, the polyvinylidene fluoride (PVDF) membranes were modified to improve their performance towards desalination of simulated saline water. Particularly, acid treated carbon nanotubes (f-CNTs) and cellulose nanocrystals-capped silver nanoparticles (CNC-AgNPs) were incorporated into the PVDF matrix prior to casting. Simulated seawater (33.59 g/L) was used as the feed during DCMD tests. The modified membrane displayed improved tensile strength, surface roughness, and hydrophobicity. Interestingly, minimal leaching of AgNPs (0.378 ± 0.0628 ppm) was recorded within 72 hrs. Although water flux (0.179 ± 0.0303 kg/m2/hr) remained relatively low, salt rejection (99.8%) improved upon incorporation of NPs. This provides a one-step solution towards better performance in MD for recovery of freshwater from high saline seawater.